1992
DOI: 10.1080/10408399209527603
|View full text |Cite
|
Sign up to set email alerts
|

Food legumes in human nutrition: A personal perspective

Abstract: Perhaps with the notable exception, and that only in recent years, of red meat, which contributes dietary saturated fats and cholesterol, two well-known reasons in the etiology of heart-related disorders, no single group of foods has been portrayed in such negative terms as the food legumes traditionally have been during the last 50 years of research in food science and human nutrition. Even more alarming are the trends of continued research on such aspects as the deficiency of sulfur-amino acids (both by amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 94 publications
1
46
1
6
Order By: Relevance
“…Food legumes constitute a major source of nutrients such as proteins, lipids, carbohydrates, and other important substances such as fibre, minerals and vitamins (Deshpande, 1992) which are necessary for human and animal health. Similarly, they contain anti-nutritional components such as saponins, tannins, phytates, lectin/haemagglutanin, oxalates, polyphenol, among others, which hinder the body from digesting the nutrients in pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Food legumes constitute a major source of nutrients such as proteins, lipids, carbohydrates, and other important substances such as fibre, minerals and vitamins (Deshpande, 1992) which are necessary for human and animal health. Similarly, they contain anti-nutritional components such as saponins, tannins, phytates, lectin/haemagglutanin, oxalates, polyphenol, among others, which hinder the body from digesting the nutrients in pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Lentil seeds are used nowadays in the folk medicine of many ethnicities to treat different illnesses. They are used orally to treat diabetes, topically as a water-paste to treat skin infections, and burns, after being roasted, milled, and applied directly to the affected areas (42,43). Houshmand et al revealed that hydroalcoholic extract of red lentil had protective effect on catatonia induced by perphenazine in rats (44).…”
Section: Discussionmentioning
confidence: 99%
“…O feijão-comum (Phaseolus vulgaris, L.) é um alimento básico em vários países, constituindo-se em importante fonte de proteína, carboidrato, fibra e micronutrientes (Deshpande, 1992;Acevedo et al, 1994). Entretanto, uma parte dos nutrientes existentes no grão nem sempre é aproveitada pelo consumidor devido à presença de fatores antinutricionais, dentre estes estão os fitatos e os taninos.…”
Section: Nota Científicaunclassified